Hillary Clinton in the news : gender and authenticity in American politics - Parry-Giles, Shawn J., 1960- (University of Illinois Press, 2014)
"The charge of inauthenticity has dogged Hillary Clinton from the moment she entered the national spotlight. Shawn J. Parry-Giles examines questions about the authenticity and political image-making of the the former first lady-turned-senator-turned presidential candidate and the media's representation of her as one of "the most loved and hated presidential wives in American history." Parry-Giles tracks Clinton as she assumed an array of roles from surrogate campaigner, legislative advocate, and financial investor to international emissary, scorned wife, and political candidate. After the 1992 campaign, the health care debate, and the Whitewater controversy, a familiar news framing developed, which disparaged Clinton for her outspoken, overly visible political presence. In this backlash, news frames stressed her transgressions in overstepping the boundaries of authentic womanhood and first lady comportment. During the Lewinsky scandal, the victimhood frame furthered her characterization as a scorned woman admonished to the private sphere as wife and mother. Parry-Giles' longitudinal study magnifies how the coverage that preceded Clinton's entry into electoral politics was grounded in her earliest presence in the national spotlight. Most disturbingly, once Clinton vied for office in her right, the news exuded a rhetoric of sexual violence, motivated by portrayals of her as an inauthentic political woman acting outside the confines of her gender. While Clinton's defiance was awe-inspiring and precedent setting, the magnitude of the disciplining and harsh rhetoric that she faced served as a warning to other women who dared to enter the political arena and violate the protocols of authentic womanhood"--